Engineering the Saccharomyces cerevisiae β-oxidation pathway to increase medium chain fatty acid production as potential biofuel - Chen, Liwei (2014)
Fatty acid-derived biofuels and biochemicals can be produced in microbes using β-oxidation pathway engineering. In this study, the β-oxidation pathway of Saccharomyces cerevisiae was engineered to accumulate a higher ratio of medium chain fatty acids (MCFAs) when cells were grown on fatty acid-rich feedstock. For this purpose, the haploid deletion strain Δpox1 was obtained, in which the sole acyl-CoA oxidase encoded by POX1 was deleted. Next, the POX2 gene from Yarrowia lipolytica, which encodes an acyl-CoA oxidase with a preference for long chain acyl-CoAs, was expressed in the Δpox1 strain. The resulting Δpox1 [pox2+] strain exhibited a growth defect because the β-oxidation pathway was blocked in peroxisomes. To unblock the β-oxidation pathway, the gene CROT, which encodes carnitine O-octanoyltransferase, was expressed in the Δpox1 [pox2+] strain to transport the accumulated medium chain acyl-coAs out of the peroxisomes. The obtained Δpox1 [pox2+, crot+] strain grew at a normal rate. The effect of these genetic modifications on fatty acid accumulation and profile was investigated when the strains were grown on oleic acids-containing medium. It was determined that the engineered strains Δpox1 [pox2+] and Δpox1 [pox2+, crot+] had increased fatty acid accumulation and an increased ratio of MCFAs. Compared to the wild-type (WT) strain, the total fatty acid production of the strains Δpox1 [pox2+] and Δpox1 [pox2+, crot+] were increased 29.5% and 15.6%, respectively. The intracellular level of MCFAs in Δpox1 [pox2+] and Δpox1 [pox2+, crot+] increased 2.26- and 1.87-fold compared to the WT strain, respectively. In addition, MCFAs in the culture medium increased 3.29-fold and 3.34-fold compared to the WT strain. These results suggested that fatty acids with an increased MCFAs ratio accumulate in the engineered strains with a modified β-oxidation pathway. Our approach exhibits great potential for transforming low value fatty acid-rich feedstock into high value fatty acid-derived products.